Analysis of Traffic Jams: Cases of Congestion Caused U-Turns on Jalan Gajah Mada, Batam - Fakhri Alfitra; Usmanul Hayadi Umar (Fakultas Teknik Sipil dan Perencanaan, 2023)
U-Turn is used as a special access for drivers who want to change lanes while they are moving. However, the problem that often occurs is this. Intersections can be the main cause of congestion on the road. In the case of the U-Turn on Jalan Gajah Mada. Traffic jams are often caused by this, especially in the afternoon during working hours. According to the 1997 Indonesia Road Capacity Manual, this study attempts to evaluate the performance of intersections and determine whether they are the main cause of persistent traffic congestion. The techniques used to obtain data are observation and documentation. The results showed that the road capacity value was 1311 pcu/hour. Value of traffic volume direction Baloi – Tiban 1421 pcu/hour. 16.00 - 18.00 is like making a U-turn with an average travel time of 08'36